Tax made less taxing a reviewer with codals and cases - Ingles, Ignatius Michael D. (Rex Book Store, 2025)
General principles of taxation -- Income tax-- Donor's tax-- Value-added tax-- Government's remedies-- Taxpayer's remedies-- Court of tax appeals-- Local government taxation-- Real property taxation-- Tariff and customs code of 1978, as amended by the Customs Modernization and Tariff Act (R.A. 10863 or the CMTA)